A new approach to the gas dynamics equation: An application of the decomposition method - Evans, DJ; Bulut, H (Taylor & Francis Ltd, 2002)
The Adomian decomposition method is used to implement the homogeneous gas dynamics equations. The analytic solution of the equation is calculated in the form of a series with easily computable components. The homogeneous problem is quickly solved by observing the self-canceling noise terms whose sum vanishes in the limit. Comparing the methodolgy with some other known techniques shows that the present approach is effective and powerfull. Many test modeling problems from mathematical physics, both linear and nonlinear are discussed to illustrate the effectivness and the performance of the decomposition method.
Keywords: nonlinear gas dynamics equation; the decomposition method